Heat-Induced Photosynthetic Responses of Symbiodiniaceae Revealed by Flash-Induced Fluorescence Relaxation Kinetics - Mohammad Aslam, Sabit; Patil, Priyanka Pradeep; Vass, Imre; Szabó, Milán (Frontiers in Marine Science, 2022)
Symbiodiniaceae live in endosymbiosis with corals. In the last few decades, mass bleaching events have occurred in the coral reefs, causing damage in the ecosystem and the associated species. Global temperature increase is affecting the algae, disturbing the whole symbiosis and leads to coral bleaching. However, the heat tolerance is strongly determined by the species (formerly genetic clades) harbored by the coral host. We assessed three different strains of Symbiodiniaceae family, i.e., Fugacium kawagutii (CS156), Symbiodinium tridacnidorum (2465), and Symbiodinium microadriaticum (2467), which display different heat tolerance under heat stress conditions. Flash-induced chlorophyll fluorescence relaxation is a useful tool to monitor various components of the photosynthetic electron transport chain and the redox reactions of plastoquinone pool. We observed the appearance of a wave phenomenon in the fluorescence relaxation by heating the strains in combination with microaerobic conditions. The characteristics of this fluorescence wave were found to be strain-specific and possibly related to the transient oxidation and re-reduction of the plastoquinone pool. The appearance of the wave phenomenon appears to be related to cyclic electron flow as well because it is accompanied with enhanced post-illumination chlorophyll fluorescence rise. These results will potentially reveal further details of the role of cyclic electron transport in Symbiodiniaceae and its relevance in heat stress tolerance.